ANALISIS KEMAMAMPUAN KOMUNIKASI SISWA MENENGAH TERHADAP RESILIENSI MATEMATIS - Citra - Rahmawati; Luvy Sylviana Zhanty (IKIP Siliwangi, 2019)
The purposes of this study are to identify the level of communication skills and mathematical resilience of junior high school students and to find out their mistakes in finishing communication-based questions. The method used in this study is descriptive quantitative method. This study is conducted in an Islamic school namely MTs Al Basyariyah located in Bandung, Indonesia. Performing as the respondents of this study are 36 students of class IX-B. To collect the data, this study employs a communication-based question diagnostic test and a questionnaire on student resilience. The results of the study show that (1) most of the students find it difficult to do question number one whose indicator is written text; (2) students’ skill on doing communication-based questions is still low; and (3) there is not significant correlation between students’ communication skills and their resilience. To cope with these phenomena, it is recommended that teachers use learning strategies that are able to enhance students’ conceptual understanding so that their communication skills can be achieved.